Pengaruh Komunikasi Interpersonal Dosen Pada Mata Kuliah Statistik Ekonomi II Terhadap Motivasi Belajar mahasiswa Pada STIMI Meulaboh - Nur Fajri; Yenni Muflihan; Eka Syani (Jurnal Inotera, 2022)
This study aims to determine the effect of lecturer interpersonal communication on student learning motivation at STIMI Meulaboh. The dependent variable in this study is the student's learning motivation while the independent variable is the lecturer's interpersonal communication. The research method used in this study is to use multiple linear regression. Based on the results of the study, the value of sig < 0.05 in other words H0 accepted, meaning that interpersonal communication between lecturers (openness, empathy, and support) had an effect on student learning motivation in the economic statistics course II at STIMI Meulaboh.